The Philosophical Foundation of English Textbook “Buku Bahasa Inggris” for Vocational High School Student Grade XII 2018 Revision - Uyunnasirah Hambali; Abd Rajab; Rasmi Rasmi; Wahyuddin Wahyuddin (Jurnal Studi Guru dan Pembelajaran, 2021)
English Textbook is the one important thing for teaching English in the school. Thus, the teacher should know that English textbook function and the philosophical foundation. This study aimed to find out the philosophical foundation of Buku Bahasa Inggris for Senior High Schools Grade XII 2018 revision. This study used content analysis inferential. The object of the study was English textbook “Buku Bahasa Inggris” for Vocational High School grade XII 2018 revision. The step of the study began to read the English textbook, making note, coding the data, collecting the data, categorize and classify and analysis. Sample of this textbook were 4 chapters of 11 chapters that were chapter 1,2,3 and 5. Inferential data of this study that found by using construct analysis. The result of construct analysis show some conclusion. Based on analysis content inferential, the researcher found six of philosophical foundation of English textbook of Buku Bahasa Inggris for Vocational High School Grade XII 2018 revision. They were Progressivism, Social Reconstruction, Humanism, Existentialism, Perennialism, and Essentialism. Thus, Progressivism, Social Reconstruction and Humanism were the most appearing on the English textbook “Buku Bahasa Inggris”. The researcher conclude that the English textbook applied student centered learning and problem solving where we can find from the English textbook.